Kandidat Probiotik Ramah Lingkungan Dari Batang Pisang (Musa Paradisiaca) Untuk Peningkatan Produksi Ikan Nila (Orechromis niloticus) - Gde Raka Angga Kartika; Endang Wulandari Suryaningtyas (Journal of Marine and Aquatic Sciences, 2021)
One treatment to increase the productivity of tilapia fish farming is by administering probiotics. Natural probiotics, besides it is safe for consumers, it is also very environmentally friendly because it is obtained from natural. The stem of banana (Musa paradisiaca) is organic waste that is commonly found in Indonesia. In the banana stems, they contain carbohydrates, protein, water, and essential minerals that can be used by microorganisms (bacteria) to evolve. Research conducted explorative research, by identifying lactic acid bacteria (BAL) potentially isolated from the banana stem probiotics (Musa paradisiaca) In specific media MRSA BCP and the addition of probiotics banana stems on Tilapia fish feed to see the effectiveness of the use of probiotics in tilapia culture. The result showed the density of lactic acid bacteria probiotic banana stems on the first day 0, day three: 1.63 x 107, the seventh day: 3:20 x 107, and the fourteenth day: 0. Results of testing the addition of probiotics in the feed of tilapia showed that tilapia given feed with probiotics that had specific growth rate and absolute growth is higher than the tilapia fed without probiotics.